The Mobility of Hinduism Sociocultural Race at Pura Agung Wanakertha Jagatnatha, Central Sulawesi - IK Suparta; I Putu Gelgel; I Wayan Subrata (International Journal of Interreligious and Intercultural Studies, 2023)
The Temple is a place of worship for Hindus that was built to strengthen belief in God. As time goes by, there is a shift in the function of temples, one of which is Pura Agung Wanakertha Jagatnatha, Central Sulawesi that has overlapping management systems that affect the sacredness of the temple. The aim of this research is to explore the factors causing sociocultural mobility, dissected using deconstruction theory, analyzing the process of sociocultural mobility of Hindus, dissected using modernism theory, and analyzing its implications for the religious, socio-cultural and economic aspects of society, dissected using reception theory. This research used a qualitative research with sociology of religion approach. The methods used are observation, interviews and literature study. Data analysis techniques used qualitative interpretive data analysis, checking the validity of the data using triangulation. The results of this research show that: The factors causing the sociocultural mobility of Hindus are population change, development orientation, human education, ideological consensus, environment, worldview, management organization, political system (identity politics), development of science and technology. The process of sociocultural mobility of Hindus occurs in an evolutionary manner, in each period there are also changes in material infrastructure, social structure and ideological superstructure. The implications of sociocultural mobility for religious life include increasing and decreasing the religious quality of society. The implications for the social and cultural life of society include the formation of new rules and kinship groups, increasing and decreasing the role of organizations, and cultural acculturation. The implications for the economic life of society include the formation of community economic institutions, the decline and increase in economic management, and the occurrence of commodification in temples